Krisis moral di era digital dan tantangan etika bagi mahasiswa - Khasanaturrofiah, Amira Dian; Putra, Rheno Rantau; Zuhayrah, Wafa Soraya (Maliki Interdisciplinary Journal, 2026)
The challenge that students must face today is the moral and ethical crisis in the digital era. Technological developments in the digital era have brought many conveniences to the academic process, such as fast access to information, and the presence of artificial intelligence. However, this convenience also creates new challenges for students, especially in terms of academic ethics. Phenomena such as plagiarism, academic dishonesty, data manipulation, and the use of technology without considering moral responsibility are increasingly emerging issues in higher education environments. Through the perspectives of ontology, epistemology, and axiology in the philosophy of science, the moral crisis can be explained as the result of the use of knowledge that does not adhere to ethical values. Knowledge should be developed through wise means and used responsibly. The crisis arises when students view technology merely as a tool for achieving quick results without regard for honesty and integrity. To address this problem, students need to cultivate ethical self-awareness, while educational institutions also play a role in strengthening moral development, digital literacy, and enforcing academic regulations. The integration of science and morality is crucial for digital technology to be utilized wisely and to create an ethical, honest, and responsible academic culture.